The Selection and Termination of Investment Management Firms by Plan Sponsors - GOYAL, AMIT; WAHAL, SUNIL (Journal of Finance, 2008)
ABSTRACT We examine the selection and termination of investment management firms by 3,400 plan sponsors between 1994 and 2003. Plan sponsors hire investment managers after large positive excess returns but this return‐chasing behavior does not deliver positive excess returns thereafter. Investment managers are terminated for a variety of reasons, including but not limited to underperformance. Excess returns after terminations are typically indistinguishable from zero but in some cases positive. In a sample of round‐trip firing and hiring decisions, we find that if plan sponsors had stayed with fired investment managers, their excess returns would be no different from those delivered by newly hired managers. We uncover significant variation in pre‐ and post‐hiring and firing returns that is related to plan sponsor characteristics.